Optimization of optimal pressure parameters for filtering chyle plasma under low-temperature conditions - GAO Zhanhai; JI Xiaohua; ZHANG Fumin; HUANG Zhanhua; CHENG Wei (Zhongguo shuxue zazhi)
[Objective] To explore the optimal pressure parameters for chyle plasma filtration under low-temperature conditions, and to improve the quality of chyle plasma treatment and filtration efficiency by improving experimental methods. [Methods] The filtration efficiency and filtration time of 30 severe chyle plasma samples under conventional preparation environment pressure and under preparation environment with a controlled filtration membrane pressure difference of 0.5 bar were compared. [Results] The absorbance of severe chyle plasma samples before and after filtration under two different preparation pressures was statistically significant (P<0.05), and both achieved the expected filtration effect. Under the preparation environment of controlling the pressure difference of the filtration membrane to 0.5 bar, the filtration was faster and with better effect, which was statistically significant compared to the conventional preparation environment pressure (P<0.05). [Conclusion] By selecting the optimal pressure parameters for filtering chyle plasma under low-temperature conditions, the efficiency of chyle plasma filtration under low-temperature conditions has been improved, and the practicality and reliability of low-temperature filtration technology have been enhanced.